If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v = w(w + 3)(2w) Reorder the terms: v = w(3 + w)(2w) Remove parenthesis around (2w) v = w(3 + w) * 2w Reorder the terms for easier multiplication: v = 2w * w(3 + w) Multiply w * w v = 2w2(3 + w) v = (3 * 2w2 + w * 2w2) v = (6w2 + 2w3) Solving v = 6w2 + 2w3 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Simplifying v = 6w2 + 2w3
| 2h+5=75 | | 2x^2-4=-5x | | 3.2-0.04= | | y/5-0.4=0.33-y | | 3x/7y | | .1070=x+(x-.056)(1.1)(1-.35) | | 10.70=x+(x-.056)(1.1)(1-.35) | | 5x-8=6-2 | | -12=x/5 | | 12=6+6(x-11) | | 4+3(2x-1)=19 | | 8x-3x+6x-x=5-14+6+3 | | 6/8x=9 | | .25x-0.08=.167x+.167 | | 0.5x^2-0.25x+0.1= | | 9x-9-7x=-x+6 | | Y=0.5x^2-0.25x+0.1 | | 8x-14-3x-6+6x-x=5-14+6+3 | | 2x-3.33=6-0.33x | | 9x-9-7x=-x+x | | x-3x-5=35 | | 18=x^2-x-2 | | x^2+6x-33=0 | | 6-2(3-2x)+6=32 | | 19=8+k | | 38=2L+2(4) | | .25x-1=.5x+1.5 | | (3+z)(3z-8)=0 | | 6x-36/x^2-6x | | -6x+2=3x+1 | | d/2-4=-11 | | .5x+2-.67x+.67=3 |